Rural banking in China: a case of centralization?. Issue 2 (4th May 2017) - Yeung, Godfrey; He, Canfei; Zhang, Peng
ABSTRACT: Four types of banking institutions responded differently to the drive to centralize Chinese rural banking operations. In 2009 city commercial and market-oriented banks had a higher density of outlets in economically developed than in less developed counties, as expected, while rural banking institutions had an unexpectedly higher density in non-agricultural than in agriculture-based counties. Circumstantial evidence suggests that the wholly state-owned and policy-oriented Agricultural Development Bank of China has invested in business-oriented activities in non-agricultural counties. These banking sector developments could have long-term policy implications for rural development in China.